A guide and advice for economists on the US junior academic job market (2011-2012 edition) - John Cawley (Institute for the Study of Labor (IZA), 2011)
This guide, updated for the 2011-12 job market season, describes the U. S. academic market for new Ph.D. economists and offers advice on conducting an academic job search. It reports findings from published papers, describes practical details, and provides links to internet resources. Topics addressed include: preparing to go on the market, applying for academic jobs, signaling, interviewing at the ASSA meetings, campus visits, the secondary market scramble, offers and negotiating, diversity, and dual job searches.
urn:nbn:de:101:1-20111011193
Keywords: A11; J0; J44; A23; 330; academic labor market; market for economists; salaries; Ökonomen; Akademiker; Arbeitsmarkt; Lohn; USA